Teacher-Student Interaction and Achievement in a Seventh-Grade Mathematics Class - Hart, Laurie E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
The purposes of this study are to describe teacher-student interaction in a seventh-grade mathematics class and to examine the relationships between teacher-student interaction and achievement by race and sex. Sixteen students taught by a black male were studied. For 10 days near the middle of 45 classroom days, quantitative teacher-student interaction data were gathered. Achievement data was obtained from two standardized measures (Grade 6 Iowa Test of Basic Skills and American Junior High School Mathematics Examination) and four classroom achievement measures (Grade 6 final grade, Grade 7 November and January test grades, and Grade 7 second quarter grade). On all achievement measures, the means for the white students were higher than the means for the black students. On the teacher-student interaction measure, the black students had more total academic interactions and student-initiated academic interactions; the white students initiated more procedural interactions. The differences in means by sex were less than one-third of a standard deviation both on all three Grade 7 classroom measures and in each teacher-student interaction category. The white males and the black females had the most interactions, the most teacher-initiated interactions, and the most student-initiated interactions. (YP)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (Boston, MA, April 16-20, 1990).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Communication; Grade 7.; Junior High Schools; Mathematics Achievement; Mathematics Instruction; Mathematics Teachers; Racial Differences; Secondary School Mathematics; Sex Differences; Teacher Influence; Teacher Student Relationship; Reports, Research; Speeches/Meeting Papers